SPESIASI DAN BIOGEOGRAFI IKAN DI KAWASAN SEGITIGA TERUMBU KARANG - Fione Yukita Yalindua (OSEANA, 2021)
The coral triangle is a region with the highest hotspot of fish biodiversity in the world. Factors to explain biodiversity in the coral triangle are varied widely. Factors as well as biogeography and speciation in evolutionary processes would explain the richness of fish species. The species formation theory in fish (speciation) is divided into allopatric, sympatric, and parapatric speciations. Biogeographically, the reason of what causes high biodiversity in the coral triangle area is divided into several models, namely: the center of origin, the center of overlap, the center of accumulation, the center of survival/refugia, and the mid domain effect/null model. This article will discuss the role and contribution of each mode/hypothesis in explaining coral triangle areas' biodiversity hotspots to provide information for biodiversity conservation of reef fishes in the future.